2016
DOI: 10.1007/s40534-016-0101-y
|View full text |Cite
|
Sign up to set email alerts
|

Bluetooth as a traffic sensor for stream travel time estimation under Bogazici Bosporus conditions in Turkey

Abstract: Travel time estimation is an integral part of Intelligent Transportation Systems, and has been an important component in traffic management and operations for many years. Travel time, being spatial in nature, requires spatial sensors to measure it accurately. Bluetooth is emerging as a promising technology for the direct measurement of travel time, and is reported in a few studies from homogenous traffic conditions. At the same time, there have been no studies on the applicability of Bluetooth for travel time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…For the derivation of the ground-truth data set, LDs and microwave sensors are utilized; i.e., no actual empirical measurement of the traffic flow or travel time was performed. The results are supported by another study in Turkey, where a penetration rate of 5% was found [ 11 ]. Another field test was conducted by [ 12 ] on a freeway in Barcelona, Spain.…”
Section: Related Worksupporting
confidence: 80%
“…For the derivation of the ground-truth data set, LDs and microwave sensors are utilized; i.e., no actual empirical measurement of the traffic flow or travel time was performed. The results are supported by another study in Turkey, where a penetration rate of 5% was found [ 11 ]. Another field test was conducted by [ 12 ] on a freeway in Barcelona, Spain.…”
Section: Related Worksupporting
confidence: 80%
“…A few examples of the use of mobile data for understanding activity chains and trajectories are presented in [3,4] while Bluetooth and Floating Car Data are used for the same purpose in [5,6], respectively.…”
Section: Probe Datamentioning
confidence: 99%
“…Correct categorisation of the detected passing objects can be a challenging task as addressed in [175], [246], [242], [115], [182], [180]. For example, it is hard to distinguish a Bluetooth device, which belongs to a running person, from a slowly moving vehicle in a heavily congested area.…”
Section: Uncertainties In the Detection Of The Type Of Bluetooth Devicesmentioning
confidence: 99%
“…Bluetooth traffic monitoring devices record any detected Bluetooth devices, which can belong to a vehicle, printer, smartwatch, etc. Identifying and removing unrelated traffic data, vehicles which stop or park between two consecutive detections for a recognisable time, and obtaining an accurate travel-time (TT) are still challenges associated with the utilisation of BTMS for real-time traffic monitoring as addressed by [110], [175], [246], [242], [115], [182], [180]. In this chapter, I introduce an algorithm for Multi-Tenancy Detection in the collected Bluetooth data (MTDiBT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation